Implementasi Six Sigma dalam Pengendalian Defect Product pada Engine Assembly Line PT XYZ - Restu Faidin; Supriyati Supriyati; Supriyanto Supriyanto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze and reduce oil leakage defects in the Oil Leak Test process at the Engine Assembly Line of PT XYZ using the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Research data were collected from May to October 2025 with a total production of 73,644 units and 381 defects identified. The measurement results showed a Defects Per Million Opportunities (DPMO) value of 398 with a sigma level of 4.85. Pareto analysis indicated that the dominant defect occurred in the damper pulley area. Fishbone analysis identified defect causes related to human, machine, method, material, and environmental factors. Improvement actions included torque wrench interlock implementation, automatic air blow installation, additional component inspection, and material protection. After implementation, the DPMO decreased to 208 and the sigma level increased to 5.03. The results indicate that the Six Sigma method effectively improves the quality of the Oil Leak Test process.